Mutation of the Transcriptional Regulator YtoI Rescues Listeria monocytogenes Mutants Deficient in the Essential Shared Metabolite 1,4-Dihydroxy-2-Naphthoate (DHNA) - Chen, Grischa Y. (Infect Immun, 2019)
Listeria monocytogenes, a Gram-positive, facultative intracellular pathogen, survives and replicates in the cytosol of host cells. Synthesis of 1,4-dihydroxy-2-naphthoate (DHNA), an intermediate of menaquinone biosynthesis, is essential for cytosolic survival of L. monocytogenes independent from its role in respiration. Here, we demonstrate that DHNA is essential for virulence in a murine model of listeriosis due to both respiration-dependent and -independent functions. In addition, DHNA can be both secreted and utilized as an extracellular shared metabolite to promote cytosolic survival inside host macrophages. To understand the role(s) of DHNA in L. monocytogenes intracellular survival and virulence, we isolated DHNA-deficient (ΔmenD strain) suppressor mutants that formed plaques in monolayers of fibroblasts. Five ΔmenD suppressor (mds) mutants additionally rescued at least 50% of the cytosolic survival defect of the parent ΔmenD mutant. Whole-genome sequencing revealed that four of the five suppressor mutants had independent missense mutations in a putative transcriptional regulator, ytoI (lmo1576). Clean deletion and complementation in trans confirmed that loss of ytoI could restore plaquing and cytosolic survival of DHNA-deficient L. monocytogenes. RNA-seq transcriptome analysis revealed five genes (lmo0944, lmo1575, lmo1577, lmo2005, and lmo2006) expressed at a higher level in the ΔytoI strain than in the wild-type strain, whereas two genes (lmo1917 and lmo2103) demonstrated lower expression in the ΔytoI mutant. Intriguingly, the majority of these genes are involved in controlling pyruvate flux. Metabolic analysis confirmed that acetoin, acetate, and lactate flux were altered in a ΔytoI mutant, suggesting a critical role for regulating these metabolic programs. In conclusion, we have demonstrated that, similar to findings in select other bacteria, DHNA can act as a shared resource, and it is essential for cytosolic survival and virulence of L. monocytogenes. Furthermore, we have identified a novel transcriptional regulator in L. monocytogenes and determined that its metabolic regulation is implicated in cytosolic survival of L. monocytogenes.